2009
DOI: 10.1007/s10552-009-9350-y
|View full text |Cite
|
Sign up to set email alerts
|

Coffee, black tea and risk of gastric cancer

Abstract: Our investigation, based on a uniquely large dataset, provides convincing evidence that coffee and black tea consumption is unlikely to be strongly associated with gastric cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
6
0
2
Order By: Relevance
“…The observed gradient across SES factors significantly reflects the importance of lifestyle factors in cancer prevalence. Policies should aim to curb universal risk factors causing cancerous tumors such as tobacco and alcohol, poor diet (insufficient fruit or vegetable intake), overweight and obesity, physical inactivity, chronic infections from Hepatitis B and C virus and environmental risks including ionizing and non-ionizing radiation [5, 8,6668]. These issues are critical because India has high prevalence of such risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The observed gradient across SES factors significantly reflects the importance of lifestyle factors in cancer prevalence. Policies should aim to curb universal risk factors causing cancerous tumors such as tobacco and alcohol, poor diet (insufficient fruit or vegetable intake), overweight and obesity, physical inactivity, chronic infections from Hepatitis B and C virus and environmental risks including ionizing and non-ionizing radiation [5, 8,6668]. These issues are critical because India has high prevalence of such risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the only case-control study that investigated the association of decaffeinated coffee consumption with gastric cancer risk, reported no association. 24 Stratification by anatomical site suggested a positive association between gastric cardia cancer risk and consumption of total and caffeinated coffee. To our knowledge, only two studies have examined the relationship between coffee consumption and gastric cardia cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] Epidemiological studies that examined the association between either coffee or tea consumption and gastric cancer risk have shown inconclusive results. Although some case-control and cohort studies indicated no association between coffee consumption and risk of gastric cancer, [24][25][26] others have shown an inverse association or a positive association. [27][28][29] A meta-analysis (2006) of 23 studies reported no significant association between coffee consumption and gastric cancer risk.…”
mentioning
confidence: 98%
“…Entretanto, pesquisas revelam que a ingestão de cafeína em excesso pode causar vários distúrbios no organismo como dores de cabeça, irritabilidade, insônia, doenças coronarianas e até evoluir para alguns tipos de câncer (GALLUS et al, 2009;MONTELLA et al, 2009;SIN et al, 2009;TANG et al, 2009). Devido a esses estudos, a procura pelo café descafeinado tem aumentado consideravelmente, sendo até mesmo recomendado por médicos.…”
Section: Introductionunclassified